LENGUAJE Y APRENDIZAJE EN LA UNIDAD EDUCATIVA ISABEL DE GODÍN”, RIOBAMBA, PERÍODO OCTUBRE 2018 – MARZO 2019” - Piñaloza Salazar, Cristina Alejandra (2019)
The objective of this research project is to determine the relationship between oral language and the auditory learning style of students in the 4th year of Basic General Education, parallel "A" and "B" in the Educational Unit "Isabel de Godín", in the period October 2018 - March 2019. Theoretically, the variables of language and learning study were described by obtaining information through books, magazines and websites; the methodology used for its design is non-experimental because the variables were not manipulated; the type of investigation is descriptive and correlational; by the level of field to be made in the place of the facts; the population was the children of the fourth year of basic education parallel "A" and "B", the sampling is not probabilistic and intentional because it worked with the 38 students; the techniques were the psychometric tests, the evaluation instruments for the first variable the Elo Test was used and for the second variable the Learning Styles Test, by means of which the data were obtained in order to reach the conclusion prior to the application of the respective statistician if there is a significant correlation, since oral language is important at the time of learning, which favors the development of reading and writing in children.